Upaya Meningkatkan Kemampuan Bahasa Inggris Melalui Outdoor Activity Berbasis Pembelajaran Tematik di LKP BBC Cabang Koja - Pristanto Ria Irawan; Miftahudin Miftahudin; Allya Saputro; Joelianti Dwi. S; Syamsul Bahri; Supriyadi Supriyadi; Sopian Sopian (Journal on Education, 2023)
This study aims to get an overview of the implementation of activities outdoor activity thematically based on improving English skills at the BBC's English Language Course and Training Institute, Koja branch, North Jakarta. This descriptive qualitative research uses interviews, questionnaires, and documentation. The results of the research show that thematic learning is done through outdoor activity in accordance with the syllabus, the implementation schedule is on time, the location is in accordance with the thematic, and based on an assessment of student abilities to listen with dominance good, the average value is 85 (range of scores 80-90), reading ability students get an average value 95 with mastery Very good, (score range 90-100), writing ability students get an average value 83 (80-90 grade range) with mastery Good, and students' ability to speak mastery Good, with value average 87 (range of scores 80-90)